PENGARUH PERPUTARAN KAS DAN PERPUTARAN PIUTANG TERHADAP PROFITABILITAS PADA PT.INDOFOOD SUKSES MAKMUR TBK - Gita Eliya Cahyani; Subagyo Subagyo; Andrea Gideon (CAHAYA AKTIVA, 2019)
This study aims to determine and examine the effect of cash turnover and receivable turnover on profitability at PT. Indofood has prosperous success. This study uses the population of all financial reports (quarterly) PT. Indoodood Sukses Makmur TBK listed on the Indonesia Stock Exchange (IDX) for the period 2010-2017. Based on predetermined criteria, 32 samples were obtained.The data analysis technique used is multiple regression analysis and with the help of SPSS version 16.0. in this study experienced the disposal of outlier data in order to be able to normal distribution and disposal of Company Size variables as the cause of multicollinearity.Test results show that the Cash Turnover variable (X1) has a significant negative effect on ROA while the Receivable Turnover variable (X2) has a significant positive effect on ROA. The probability value of the Cash Turnover variable (X1) is 0.569 against ROA. Receivable Turnover (X2) has a significant positive effect on ROA. With the probability value of the Receivable Turnover variable is 0.001 against ROA assuming the value of the other variables remains constant. This shows that if the Receivable Turnover is high, then ROA will increase. And F Test results show that cash turnover and receivable turnover have a simultant effect on profitability that is 0.02. Keywords: ROA, Cash Turnover, Receivable Turnover